Análise do grau histológico e marcadores imunohistoquímicos para a identificação de pacientes com câncer de mama luminal de alto risco - Luz, Felipe Andrés Cordero da (2022)
Background: The luminal subtype (ER and/or PR-positive, HER2-negative) account for approximately 70% of newly diagnosed breast cancer patients. Although is better prognosis, approximately 30% of them develop late relapse. Identfying those patients is of interest to treat them correctly and improve survival. Methods: Five hundred seventhy-two (572) non-metastatic (I-III) invasive ductal breast carcinoma patients with a median follow-up of 65.35 months (3.67 – 247.40) were enrolled, being 448 cases of luminal breast cancer and 124 cases of triple-negative breast cancer. Optimal cutoffs for Ki-67 and semiquantitative hormone receptor expression were established by survival analysis for continuous factors. Stepwise Forward Wald time-dependent Cox regression were performed to discriminate independent factors with increased prognosis power. Results: It was observed that patients with histological grade 1/2 tumors with high Ki-67 expression (>12%) and low semiquantitative hormone receptor expression (≤4+) behaved similarly to invasive ductal breast carcinoma grade 3 and were grouped. Such patients have distant metastasis-free survival [adjusted HaR: 0.520 (0.238 – 1.132), p=0.099] and overall survival [ajusted HaR: 0.761 (0.374 – 1.550), p=0.452] similar to triple-negative breast cancer, including therapy in the models. In association with tumor size and lymph node metastases, this classification improved the standard risk classification. Conclusion: The proliferation index by Ki-67 expression, in addition to the semiquantitative expression of hormone receptors, efficiently discriminates patients with grade 2 and grade 1 non-metastatic breast cancer with a good prognosis from those with a worse prognosis similar to triple-negative breast cancer.